Estado nutricional en pacientes con paladar y labio fisurado. Fundación Operación Sonrisa, 2018 - Jara Pereira, Gianella Betsabeth (2019)
This research aimed to relate the nutritional status to the pathologies of the cleft palate and/or cleft lip of the patients treated at the Operation Smile Ecuador. 120 clinical records were donated by the foundation from campaign of July 2018 considering the Inter-Institutional Agreement of Academic and Scientific Cooperation signed with the National University of Chimborazo. 31 medical records of patients with cleft palate and/or cleft lip were selected who fulfilled all the selection criteria. The analysis of the nutritional status of each of the patients was carried out to determine his/her current diagnosis with the help of the WHO AnthroPlus software in order to know the relationship between the nutritional diagnosis and the cleft palate and/or cleft lip condition of the patient. In addition, the type of fissure that prevails and the gender in which more cases occur were identified. The Pearson Chi-square was used to carry out the respective statistical analyzes. The results showed that there is no significant relationship between the pathologies and the nutritional status, since the value of significance (p) was greater than 0.05. So, it was concluded that the nutritional status of children was not necessarily affected by the presence of fissures in the palate or lip, however, 48.4% of the population did present some type of alteration in the state nutritional